The impact of critical success factors on government IT projects : a case study of the Defence Information Infrastructure Programme - Maddison, A (Cranfield University, 2014)
Government IT mega-projects often end in costly failure, despite attempts to identify those Critical Success Factors (CSFs) that lead to project success. This raises questions about whether these CSFs are understood, applied and, if so, whether they are having an impact on the management and subsequent performance of government IT mega-projects. The literature review compared CSFs from the generic and IT project management literature to find that they are broadly similar. CSF frameworks were then assessed to find a measure of the impact of CSFs and a measure of ‘performance’ was also defined. CSFs were then identified from fifteen reports on IT and information infrastructure projects and verified against the CSFs identified in the literature to produce a synthesised list of twelve CSFs. The understanding, application and impact of these CSFs were examined through a case study of the MoD’s Defence Information Infrastructure (DII) Programme, a government IT mega-project to provide a more integrated and coherent Defence infrastructure. It was evident that the CSFs were recognised and they appeared to have been understood within the DII Programme. However, the extent to which they have been applied is variable with differing effect. Therefore, the impact that CSFs have had on the management of the DII Programme is debatable. There were areas where the project could have been managed better and, therefore, could be performing better, suggesting that the overall success of the project is potentially at risk. The overarching conclusion of this study is that, in terms of the management of the DII Programme, the impact of the identified CSFs is variable and, where they are not applied, there is an adverse effect on its performance, suggesting a causal relationship. More generally, not applying generic CSFs to project management is likely to lead to failure, but is unlikely to assure success. Unique projects operating in highly specific and complex contexts require more contingent solutions. As a result of these conclusions, further case studies are suggested, along with further study into government and MoD IT project management and the management of trust in contractual relationships.
Keywords: Project management; Programme management; Critical success factors